Research capacity in nursing: a concept analysis based on a scoping review - Qirong Chen; Mei Sun; Siyuan Tang; Aimee R. Castro (BMJ Open)
Objective As the discipline of nursing has advanced, research capacity in nursing has become increasingly important to the discipline’s development. However, research capacity in nursing is still commonly used as a buzzword, without a consistent and clear definition. The purpose of this study is to clarify the concept of research capacity in nursing by identifying its conceptual components in the relevant nursing literature using the Pragmatic Utility method.Design A Pragmatic Utility concept analysis based on a scoping review.Data sources Academic literature retrieved from PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, Scopus, Web of Science and ProQuest Dissertations and Theses (PQDT).Eligibility criteria Qualitative studies, quantitative studies, mixed method studies or literature reviews focusing on research capacity in nursing published in English between 2009 and 2019.Results Competence, motivation, infrastructure and collaboration for nursing research are the antecedents of research capacity in nursing. The attributes of research capacity in nursing are ‘non-individual level’, ‘context-embeddedness’ and ‘sustainability’. The direct outcome of research capacity in nursing is nursing research. The allied concepts identified are nursing research competency, nursing research capability and evidence-based practice capacity in nursing.Conclusions Research capacity in nursing is the ability to conduct nursing research activities in a sustainable manner in a specific context, and it is normally used at a non-individual level. Research capacity in nursing is critical for the development of the nursing discipline, and for positive nurse, patient and healthcare system outcomes. More studies are needed to further explore the allied concepts of research capacity in nursing, and to better understand relationships among these allied concepts.